An Analysis of Students’ Writing Skills in Recount Text At The Eighth Grade Students of SMP Negeri 2 KOTA Jambi - Suyadi Suyadi (Universitas Batanghari Jambi, 2017)
Abstract This research is aimed at improving teaching Writing Skills for Recount Text especially Junior High School students at SMP Negeri 2 Kota Jambi. By using qualitative method this research tries to reveal some difficulties faced by the students in writing Recount Text and giving a resolution to overcome its difficulties. The sample was taken from Eight Grade Students at SMP Negeri 2 Kota Jambi which applied a qualitative research as mentioned by Creswell (2013:334) that Qualitative research is an inquiry process of understanding based on distinct methodological traditions of inquiry that explore a social or human problems. The researcher builds complex, holistic picture, analyze words, reports detailed views of informants, and conducts the study in a natural setting. Findings of this research is considered to be good in category with the percentage of students’ level skills is 6% in very good level, 14% classified in good level, 22% classified in fair level, 28% classified in weak level and 30% classified in poor level. The students’ of writing skills in recount text that weak category, because the students have learnt recount text more than 4 meetings and the teacher have explained seriously. The findings of the research will be useful for the English teachers and the students at Junior High School in using its results as teaching strategy and learning material for the teacher and the students as well.Keywords: Recount text, writing skills, Teaching strategy, Learning materials.